Evaluating a caregiver-focused safety culture model: Effects on caregivers’ safety perception, older adults’ quality of life, and the incidence of adverse events in Indonesia - Solihin, Asri Handayani; Probosuseno; Effendy, Christantie (Belitung Nursing Journal, 2025)
Background: Older adults are increasingly vulnerable to health risks, particularly in home care environments with limited formal safety measures. In Indonesia, family caregivers play a central role in providing care; however, research on interventions to enhance the safety of older adults at home remains limited. Objectives: This study aimed to evaluate the impact of a caregiver-focused safety model, the Aging Safe from the Risk (ASRi) model, on caregivers’ perceptions of safety culture and assessed its indirect effects on older adults’ quality of life (QoL) and incidence of adverse events. Methods: A quasi-experimental study was conducted from July to November 2022, involving 135 older adult–caregiver pairs (intervention: n = 68; control: n = 67). Older adults’ QoL was measured using the modified WHO-QOL BREF (Indonesian version) and WHO-QOL OLD instruments. Family caregivers completed a Home Safety Culture (HSC) questionnaire and reported adverse events. Data were analyzed using descriptive statistics, chi-square tests, independent t-tests, Mann–Whitney U tests, Fisher’s exact tests, repeated-measures general linear models (GLM-RM), and exploratory ANCOVA within the intervention group. Results: Baseline characteristics were largely similar for older adults (age, comorbidities, fall risk, medication use) and caregivers (gender, age, education, marital status), although some imbalances were noted. Significant between-group differences were observed in the spiritual dimension (baseline p = 0.019, r = 0.202; fourth month p = 0.018, r = 0.204) and environmental dimension of safety culture (all time points p <0.001, r = 0.347-0.431), with a transient difference in the personal dimension at month one (p = 0.013, r = 0.215). QoL scores were consistently higher in the control group (p <0.001, Cohen’s d = 0.551-0.645), reflecting baseline imbalance. Adverse events decreased in the intervention group during follow-up (p <0.001, Cramér’s V = 0.343-0.364); however, the higher baseline incidence suggests that regression to the mean may have contributed to this reduction. Conclusion: The ASRi model was associated with modest improvements in caregivers’ perceptions of safety culture. Differences in QoL and adverse events should be interpreted cautiously due to baseline imbalances and potential regression to the mean. While these findings provide preliminary indications that caregiver engagement through the ASRi model may support safer home care practices, causal conclusions cannot be drawn. Randomized studies with longer follow-up are needed to confirm these effects. Trial Registry: NCT05487482 [clinicaltrials.gov]